Prevalence and Antibiotic Resistance Profile of Bacterial Pathogens in Aerobic Vaginitis: A Retrospective Study in Italy - Enrica Serretiello; Biagio Santella; Veronica Folliero; Domenico Iervolino; Emanuela Santoro; Roberta Manente; Federica Dell'Annunziata; Rossella Sperlongano; Valeria Crudele; Anna De Filippis; Massimiliano Galdiero; Gianluigi Franci; et al. (MDPI AG, 2021)
Aerobic vaginitis (AV) is a vaginal infectious condition, characterized by a high inflammatory response and/or signs of epithelial atrophy, a decrease in the amount of Lactobacillus spp. and an increase in enteric origin bacteria. AV, often misdiagnosed, is difficult to treat due to the emerging spread of multi-drug resistant bacterial strains. The present study aimed to define the prevalence of AV, to detect causative bacteria and their antimicrobial resistance pattern. Women 10-95 years old, admitted to San Giovanni di Dio e Ruggi d'Aragona Hospital, Salerno, Italy (in the years 2015-2019) are included in the study. Bacterial identification and antibiotic susceptibility tests were carried out by VITEK® 2. Among 2069 patients, 1176 tested positive for microbial growth. A higher incidence of infection was found in the 55-64 age group. Among the pathogenic strains, 50.4% were Gram-negative, and 49.6% were Gram-positive. Escherichia coli (E. coli) (32.5%) was the most representative strain, followed by Enterococcus faecalis (E. faecalis) (29.4%), Klebsiella pneumoniae (K. pneumoniae) (7.8%) and Enterococcus faecium (E. faecium) (7.7%). E. coli showed high sensitivity to carbapenems and amikacin. K. pneumoniae carbapenems resistance was fluctuating over time. Alarming resistance to vancomycin was not recorded for Enterococci. Both strains were sensitive to teicoplanin, linezolid and tigecycline. Proper diagnosis and an effective therapeutic approach are needed to improve AV management.